The role of trust and confidential relations in broadcast of culture between generations - Tarantsei, Larisa M. (Journal of the Belarusian State University. Journalism, 2019)
The article contains an analysis of modern family research, its cultural function is singled out as an opportunity to preserve and translate the cultural and historical heritage in intergenerational communication and realization of cultural competencies of the family. Consideration of a modern family from positions of its way of life makes it possible to emphasize the traditional character of the family institution in combination with its uniqueness and originality. The author examines internal mechanisms of social and cultural translation between generations in the context of existing family relationships. The identification of the specifics of relations within three-dimensional model of trust allows us to find primary sources of the personal identity formation, to manage the channels of social and cultural translation. Studying the relationship between children and parents in the modern Belarusian family allowed the author to state a decrease in the significance of confidential relations in the broadcast of culture between generations, and also to find patterns in this process. In the author’s opinion, this is due to the loss or weakness of educational family traditions and the violation of trust in child-parent relations and in the part of the translation of culture between generations. The purpose of the article is to characterize modern approaches to the process of cultural translation in intergenerational space on the basis of analysis of the cultural function of the family, its way of life, intra-family relations in the dyad «children – parents».